Peli1 contributes to myocardial ischemia/reperfusion injury by impairing autophagy flux via its E3 ligase mediated ubiquitination of P62. (December 2022) - Yang, Jie; Tong, Tingting; Zhu, Chenghao; Zhou, Miao; Jiang, Yuqing; Chen, Hao; Que, Linli; Liu, Li; Zhu, Guoqing; Ha, Tuanzhu; Chen, Qi; Li, Chuanfu; et al.
Abstract: Autophagy flux is impaired during myocardial ischemia/reperfusion (M-I/R) via the accumulation of autophagosome and insufficient clearance, which exacerbates cardiomyocyte death. Peli1 (Pellion1) is a RING finger domain-containing ubiquitin E3 ligase that could catalyze the polyubiquitination of substrate proteins. Peli1 has been demonstrated to play an important role in ischemic cardiac diseases. However, little is known about whether Peli1 is involved in the regulation of autophagy flux during M-I/R. The present study investigated whether M-I/R induced impaired autophagy flux could be mediated through Peli1 dependent mechanisms. We induced M-I/R injury in wild type (WT) and Peli1 knockout mice and observed that M-I/R significantly decreased cardiac function that was associated with increased cardiac Peli1 expression and upregulated autophagy-associated protein LC3II and P62. In contrast, Peli1 knockout mice exhibited significant improvement of M-I/R induced cardiac dysfunction and decreased LC3II and P62 expression. Besides, inhibitors of autophagy also increased the infarct size in Peli1 knockout mice after 24 h of reperfusion. Mechanistic studies demonstrated that in vivo I/R or in vitro hypoxia/reoxygenation (H/R) markedly increased the Peli1 E3 ligase activity which directly promoted the ubiquitination of P62 at lysine(K)7 via K63-linkage to inhibit its dimerization and autophagic degradation. Co-immunoprecipitation and GST-pull down assay indicated that Peli1 interacted with P62 via the Ring domain. In addition, Peli1 deficiency also decreased cardiomyocyte apoptosis. Together, our work demonstrated a critical link between increased expression and activity of Peli1 and autophagy flux blockage in M-I/R injury, providing insight into a promising strategy for treating myocardium M-I/R injury. Graphical abstract: Unlabelled Image Highlights: We explored Peli1 in M-I/R injury and regulation of cardiomyocyte autophagy flux. Peli1 could serve as an E3 ligase of P62, mediating the ubiquitination of P62. We revealed an unknown role for Peli1 in the regulation of P62 ubiquitination. Peli1 regulates cardiomyocyte autophagy flux. We demonstrate a link between Peli1 and autophagy flux blockade in M-I/R injury.